(untitled) (Al-Academy, 2024)
This research discussed glowing-colored clays and how to use them in treating contemporary ceramic surfaces using the marbling technique to create contemporary ceramics characterized by aesthetic and expressive values. Therefore, we find that the property of Chemiluminescence helped create glowing clays with aesthetic and philosophical transformations. The research problem was summarized in the following question: Is it possible to benefit from the glowing clay technique to enrich contemporary ceramic surfaces? The research aims to identify the glowing clay technique in enriching contemporary ceramic surfaces. And revealing color-forming solutions using the glowing clay technique. It follows the descriptive approach in the theoretical framework of glowing colored clay and the marbling technique, and the experimental approach in the applied framework of self-experiment. The research hypothesizes that glowing clay technology could be used to enrich contemporary ceramic surfaces. The most important findings of the research are that the glowing clays are suitable for shaping using the marbling technique for ceramic shaping. The research also recommends the use of other techniques for ceramic modeling with glowing-colored clays. In addition, exploiting everything new and innovative in enriching contemporary ceramic surfaces.